The Ultrastructure of the Zona Fasciculata Layer of Suprarenal Gland During Pregnancy - Eroğlu, Özgür; Lortlar, Neşe; Kılıç, Sevtap; Hatipoğlu, Tahir; Ömeroğlu, Suna (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: Increased estrogen levels affect the suprarenal gland cortex, thus raising the adrenocorticotropic hormone (ACTH) during pregnancy. This study aimed to examine possible structural changes in the suprarenal gland cortex in relation to the hormonal fluctuations during pregnancy. STUDY DESIGN: The suprarenal glands of 6-day, 12-day and 18-day pregnant rats were removed and compared with those of the control group under electron microscope. RESULTS: Lipid droplets in zona fasciculata cells were observed to increase significantly in number and volume, enlarged mitochondria, active Golgi region in comparison to the control groups on 6th and 12th days of pregnancy. On day 18 were observed to lipid droplets were seen to decrease and similar characteristics with the control group. CONCLUSION: In conclusion, with the increased estrogen hormone of pregnancy, various structural changes were observed in the cortex of suprarenal glands as related to mutual interaction among secreted hormones from the suprarenal glands, hypophysis and placenta.